2020
DOI: 10.1002/ehf2.12819
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure patients with atrial fibrillation benefit from remote patient management: insights from the TIM‐HF2 trial

Abstract: Aims Atrial fibrillation (AF) is a frequent comorbidity in patients with heart failure (HF). HF patients with AF are characterized by high morbidity and increased risk of hospitalizations. We assessed the effects of remote patient management (RPM) in HF patients with AF compared with usual care (UC) in the TIM-HF2 trial. Methods and results For this post-hoc analysis, AF status at randomization was assessed in 1537 patients with HF. The primary outcome was the percentage of days lost due to unplanned cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
0
11
0
6
Order By: Relevance
“…The present exploratory analyses of prespecified eGFR-subgroups from the TIM-HF2 trial investigate the clinical effects of RPM in an HF population with impaired renal function. Other high-risk groups within the TIM-HF2 study cohort have been investigated and also showed better outcomes in the RPM group ( 31 33 ). Thus our paper extends this observation to patients with impaired vs. better renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The present exploratory analyses of prespecified eGFR-subgroups from the TIM-HF2 trial investigate the clinical effects of RPM in an HF population with impaired renal function. Other high-risk groups within the TIM-HF2 study cohort have been investigated and also showed better outcomes in the RPM group ( 31 33 ). Thus our paper extends this observation to patients with impaired vs. better renal function.…”
Section: Discussionmentioning
confidence: 99%
“…These effects were less prominent in the sinus rhythm group (P = 0.45 and P = 0.16, respectively). 41 The discussion on telemonitoring will certainly continue. This is in view of the recently published results of OSICAT (Optimization of the Ambulatory Monitoring for Patients With Heart Failure by Tele-cardiology) trial, 42 in which remote intervention was again ineffective for the primary endpoints (all-cause mortality and unplanned HF hospitalizations).…”
Section: Greenmentioning
confidence: 99%
“…▪ G-BA-Beschluss: Erstmalig wird (europaweit) eine digi- Neben der Versorgung bei HI ermöglicht eine telemedizinische Mitbetreuung auch die Betreuung von Komorbiditäten [10]. So kann durch eine frühzeitige Rhythmuskontrolle zur Detektion von Vorhofflimmern das Letalitäts-und Morbiditätsrisiko bei HI-Patient*innen deutlich reduziert werden [11]. Die intensive telemedizinische Mitbetreuung in der TIM-HF-Studie hatte zudem positiven Einfluss auf die depressive Symptomatik bei Patient*innen [12].…”
Section: Was Ist Wichtig?unclassified